How did basketball teams win EuroBasket 2015? A non-standard analysis of performance based on passes, dribbling and turnovers - Gryko, K.; Mikolajec, K.; Marszalek, J.; Adamczyk, J. G.; Molik, B.; Waskiewicz, Z.; Nikolaidis, P; Knechtle, B. (International Journal of Performance Analysis in Sport, 2020)
The aim of the study was to determine the full structure of passes during EuroBasket 2015 in the context of the execution technique, creating a passing lane, the movement of the players, the ball passing direction and passing distance. In order to provide extended data, the study also analysed individual dribbling sequences, changes of dribbling direction and turnovers. The analysis encompassed 27,840 passes, 84,080 dribbles and 1467 turnovers in all matches (n = 110) played by the eight best and the eight worst teams. Furthermore, 2030 assists were analysed to develop the model of regression. One-handed passes performed with the right hand (F = 28.74; p = 0.0028) were the most important predictor for the assists executed by the players of the eight best teams. Conversely, the most important predictor for the assists executed by the players from the weakest teams were two-handed overhead passes (F = 21.34; p = 0.0001). Today, coaches must incorporate two elements of passing technique into their training regime: primarily, one-handed passes (in particular, one-handed basic passes); and secondly, two-handed passes (overhead and chest passes). Solutions should be sought with the aim of increasing the number of inside passes, which will develop the inside play.